Relationship with reality: finitude, universality and mediation in hegelian thought - Façanha, Luciano da Silva; Carvalho, Zilmara de Jesus Viana de; Araújo, Patrício Câmara (Argumentos - Revista de Filosofia, 2015)
The objective of this text is to contribute for a look about the thought of Hegel, that closely matches the reality. For this, was chosen the perception while psychological category, which in its text is crafted in the cognitive dimension and allows you to think about a matter of philosophical tradition, with a significant density, the relationship between Uno and Multiple, being universal and that this sensitive properties. This text was used, the Phenomenology of spirit of Hegel and The years of learning Wilhelm Meister of Goethe’s in a creative dialogue with the goal of allowing a better view of the deductive Hegelian thought abstraction, cutting for this paragraphs 111 to 131 of his work in study. The texts were investigated on the highlight of the main concepts of Phenomenology in your excerpt used and its application to the narrative scenes of the novel goetheano, as well as the strategic insertions of commentators of Hegel. This approach is relevant because it is a critical reading of Hegel as a reductionist context of an unreal abstraction, as well as a contribution to further understand the different possibilities of dialogue between philosophy and literature.